(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article analyzes issues related to relations between the state and religion, reforms in the field, its legal foundations, and priorities in Uzbekistan during the years of independence. Also, the attitude towards religion, the persecution and pressures against the representatives of the industry during the Soviet period are justified.